Current Perspectives on Kisspeptins Role in Behaviour - Mills, Edouard G.; Yang, Lisa; Abbara, Ali; Dhillo, Waljit S.; Comninos, Alexander N. (Frontiers in Endocrinology, 2022)
The neuropeptide kisspeptin is now well-established as the master regulator of the mammalian reproductive axis. Beyond the hypothalamus, kisspeptin and its cognate receptor are also extensively distributed in extra-hypothalamic brain regions. An expanding pool of animal and human data demonstrates that kisspeptin sits within an extensive neuroanatomical and functional framework through which it can integrate a range of internal and external cues with appropriate neuroendocrine and behavioural responses. In keeping with this, recent studies reveal wide-reaching effects of kisspeptin on key behaviours such as olfactory-mediated partner preference, sexual motivation, copulatory behaviour, bonding, mood, and emotions. In this review, we provide a comprehensive update on the current animal and human literature highlighting the far-reaching behaviour and mood-altering roles of kisspeptin. A comprehensive understanding of this important area in kisspeptin biology is key to the escalating development of kisspeptin-based therapies for common reproductive and related psychological and psychosexual disorders.